ANALISIS PERANCANGAN SISTEM ASSET BERBASIS WEBSITE STUDI KASUS: PT LION AIR - Denny Rianditha AP (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2021)
Abstract: PT Lion Air is one of the companies engaged in the field of aviation services and is one of the cheapest and largest airline companies in Indonesia. In recording and processing the assets of PT Lion Air assets, it still uses a manual system, data is input manually. In this manual process, there are often problems in its implementation, namely the frequent occurrence of the process of requesting assets, often the loss of request documents and the difficulty of understanding the demand and data collection of assets. In this research a website-based asset information system will be created. There is also the purpose of making web-based applications so that staff who wish to submit assets can go through the web, and approval from leaders can go online without having to meet directly with the leadership. This will facilitate the staff in submitting assets. In developing the information system for asset submission using HTML, PHP and MySQL as data storage media. After going through the stages in accordance with the chosen development method, the implementation of this asset system has no further system testing, namely alpha testing, where this test uses a black box testing method that focuses on the functional requirements of the software. After alpha testing, it can be concluded that the functional system has been able to produce the expected output, with a website display that is quite interactive and makes it easy for staff to process data and request assetsKeywords: Information System Design, Asset Request, PT Lion Air.